Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1034/j.1600-0536.2003.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis from dicyclohexylmethane‐4,4′‐diisocyanate

Abstract: From August 1999 to April 2001, there was an outbreak of severe eczema at a factory manufacturing medical equipment. A glue, mainly based on the isocyanate dicyclohexylmethane-4,4'-diisocyanate (DMDI), was suspected as being the cause of the problem. 16 workers with recent episodes of eczema were patch tested with a standard series, an isocyanate series and work material. The latter consisted of, among other things, the glue, DMDI, and an amine, dicyclohexylmethane-4,4'-diamine (DMDA), which is formed when DMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 15 publications
(22 reference statements)
1
36
2
Order By: Relevance
“…Contact hypersensitivity (allergic contact dermatitis) following skin exposure to isocyanates is well documented in animals and in the clinical dermatologic literature, with sensitization confirmed with patch testing (Goossens et al 2002; Herrick 2002). Allergic contact dermatitis has been reported following skin exposure to isocyanates and polyurethane products in a number of different workplace and non-occupational settings, but has not been considered common, and is rarely reported in workers with isocyanate asthma (Alomar 1986; Frick et al 2003; Goossens et al 2002; Wilkinson et al 1991). However, allergic contact dermatitis may be more common than suspected because symptoms can be mild, workers being evaluated for asthma are frequently not asked about skin problems, and patch testing can be falsely negative (Frick et al 2004; Goossens et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Contact hypersensitivity (allergic contact dermatitis) following skin exposure to isocyanates is well documented in animals and in the clinical dermatologic literature, with sensitization confirmed with patch testing (Goossens et al 2002; Herrick 2002). Allergic contact dermatitis has been reported following skin exposure to isocyanates and polyurethane products in a number of different workplace and non-occupational settings, but has not been considered common, and is rarely reported in workers with isocyanate asthma (Alomar 1986; Frick et al 2003; Goossens et al 2002; Wilkinson et al 1991). However, allergic contact dermatitis may be more common than suspected because symptoms can be mild, workers being evaluated for asthma are frequently not asked about skin problems, and patch testing can be falsely negative (Frick et al 2004; Goossens et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…In some reports, as in our study, individuals exposed to MDI did not react to this compound in patch testing, whereas positive reactions were observed to MDA, regardless of the presence or absence of MDA in occupational setting [2,3]. Such results had been explained by the fact that MDA could be formed from MDI by hydrolysis, i.e., a reaction with water on, or in, moist skin, especially in warm working conditions provoking sweating, as was the case in the examined workplace [2,3,13,19,27]. Another hypothesis suggests that concomitant reactions to 4,4'-MDI and 4,4'-MDA may be elucidated by the pathway of reactions of MDI, leading to ureas, oligoureas and MDI conjugates with skin constituents, which can be hydrolyzed into amines, including MDA [25].…”
Section: Resultsmentioning
confidence: 81%
“…However, 7 individuals reacted to MDA, despite of lack of confirmed presence of this chemical in occupational setting. In other studies, sensitization to MDA, was frequently found together with contact allergy to MDI and MDA was considered as an indicator of MDI contact sensitization [2][3][4]19,24,25]. Simultaneous reactions to MDI and MDA were attributed to their cross-reactivity related to the similar structure [26], although according to some authors, these two chemicals could have been both primary sensitizers [3].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, allergic contact dermatitis as well as skin irritation as a result of dermal exposure have been reported by isocyanate workers. [31][32][33][34][35][36] To summarise, task based external exposure estimates indicate that in car body repair shops and industrial painting companies, mainly (spray) painters are exposed to HDI and its oligomers through inhalation as well as dermal contact. Interpretation of these short term exposure levels with respect to a total internal dose is complicated by large variability in levels within tasks, PPE use, and the lack of knowledge on the relevance of dermal exposure.…”
Section: Discussionmentioning
confidence: 99%